Characterization of phosphate structures in biochar from swine bones - Novotny, Etelvino Henrique; Auccaise, Ruben; Velloso, Marcia Helena Rodrigues; Corrêa, Juliano Corulli; Higarashi, Martha Mayumi; Abreu, Valéria Maria Nascimento; Rocha, José Dilcio; Kwapinski, Witold (Pesquisa Agropecuária Brasileira, 2012)
The objective of this work was to develop an alternative methodology to study and characterize the phosphate crystalline properties, directly associated with solubility and plant availability, in biochar from swine bones. Some phosphate symmetry properties of pyrolyzed swine bones were established, using solid state nuclear magnetic resonance spectroscopy, principal component analysis, and multivariate curve resolution analysis, on four pyrolyzed samples at different carbonization intensities. Increasing carbonization parameters (temperature or residence time) generates diverse phosphate structures, increasing their symmetry and decreasing the crossed polarizability of the pair 1H‑31P, producing phosphates with, probably, lower solubility than the ones produced at lower carbonization intensity. Additionally, a new methodology is being developed to study and characterize phosphate crystalline properties directly associated with phosphate solubility and availability to plants.
Keywords: fosfato de ossos; disponibilidade de fósforo; análise de componentes principais; pirólise; análise de resolução de curvas multivariadas; fertilidade do solo